2015
DOI: 10.1103/physrevc.91.044619
|View full text |Cite
|
Sign up to set email alerts
|

Small suppression of the complete fusion of theLi6+Zr96system at near-barrier energies

Abstract: The measurements of complete fusion cross sections for 6Li + 96Zr have been performed at energies around the Coulomb barrier by the online y-ray method. The complete fusion cross sections at above-barrier energies were found to be suppressed by ~25% . A comparison of the systematics of complete fusion suppression with the existing data for 6L i+ heavy targets with the present results shows that the systematics of the suppression factor observed for 6Li-induced fusion in the heavy mass region may not be consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Due to the low breakup threshold of the projectile nucleus, the breakup process has a significant role in description of fusion phenomenon in these reactions. In many of these studies, the measured fusion cross-sections are found to be significantly suppressed with respect to the coupled channel calculations at the above barrier energies [2][3][4][5][6][7][8][9][10][11][12][13]. Similar coupled channel calculations for fusion cross-sections in strongly bound nuclei, which account for the couplings of the inelastic and transfer processes, successfully explain the measured fusion cross-sections.…”
Section: Introductionmentioning
confidence: 66%
“…Due to the low breakup threshold of the projectile nucleus, the breakup process has a significant role in description of fusion phenomenon in these reactions. In many of these studies, the measured fusion cross-sections are found to be significantly suppressed with respect to the coupled channel calculations at the above barrier energies [2][3][4][5][6][7][8][9][10][11][12][13]. Similar coupled channel calculations for fusion cross-sections in strongly bound nuclei, which account for the couplings of the inelastic and transfer processes, successfully explain the measured fusion cross-sections.…”
Section: Introductionmentioning
confidence: 66%
“…In the case of 6 He, the suppression factors for the 64 Although the studies of the systematic behavior of the CF suppression factor discussed in this section indicate that the suppression does not depend on the mass or charge of the target, one should be careful about this conclusion. We remark that these studies were based on data for relatively heavy targets and for one of the lightest system investigated, 6 Li + 96 Zr [333], a smaller suppression was found. The suppression factor is 0.75, which corresponds to less suppression than that found for heavier targets.…”
Section: Suppression Factorsmentioning
confidence: 82%
“…This might be the indication of a trend. Although only TF data are available for lighter systems, there is some evidence that the CF suppression factor for the 6 Li + 64 Ni system is of the order of 0.87 (13% suppression) [333]. Thus, the behavior of the suppression factor in collisions of weakly bound projectiles with light and medium mass targets is not fully established.…”
Section: Suppression Factorsmentioning
confidence: 96%
See 1 more Smart Citation
“…Collisions involving weakly bound stable and unstable nuclei are interesting from the perspective of understanding both nuclear structure and nuclear reactions. Information has been obtained on clusters in nuclei [1][2][3], the effect of breakup on other reaction observables [4][5][6][7][8][9][10][11][12][13][14][15][16][17], and nuclear structure near drip lines [18,19]. In astrophysics, direct Coulomb breakup has been used to probe radiative capture reactions at low energies [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%